A cota de Andersen-Geil para distância mínima de códigos e aplicações - Silva, Otoniel Nogueira da (2013)
In this work, we study the theory of order domains with applications in linear codes, in particular; in one-point Goppa codes. We also studied some theories that served as the basis theoretical such as the theory of algebraic function fields, the theory of Gröbner bases and a brief introduction about algebraic geometry. This work aims to introduce a bound for the minimum distance of a linear code givem by Andersen-Geil in reference [1], and present a way to construct codes using the theory of order domains. Finally, we work some examples of codes with longer lengths, in this case; we use the theory of Gröbner bases as a tool.